The Influence of Audit Tenure, Auditor Competence, and Information Technology Use on Auditors’ Ability to Detect Fraud (An Empirical Study of Public Accounting Firms in South Jakarta) - Laily Ananda Afriani; Litdia Litdia (Dinasti Publisher, 2025)
The auditors’ capacity to identify fraud is crucial for preserving the integrity of financial statements and enhancing stakeholder confidence, as discrepancies in the company’s financial reporting persist. This underscores the necessity for auditors to possess sufficient professional attributes to effectively recognize and reveal signs of fraud. This study seeks to investigate characteristics influencing auditors’ capacity to detect fraud at Public Accounting Firms (KAP) in South Jakarta. This study employs a quantitative methodology focusing on auditors employed in KAP in South Jakarta, as documented in the 2025 directory. The sampling strategy employs non-probability sampling through the convenience sampling method, resulting in a sample of 90 auditors. Data analysis was conducted using outer model testing, inner model assessment, and hypothesis testing utilizing SmartPLS 4.0 software. The study’s findings indicate that audit tenure, auditor proficiency, and the application of information technology significantly influence auditors’ capacity to identify fraud.